Effects Of Acclimation Position On Detachment Of Tethered Culex Quinquefasciatus - Boyles, Ayden; Cooper, Anastasia; Silver, Kristopher (My University, 2021)
Electropenetrography (EPG) allows researchers to observe, record,and quantify the feeding behaviors of arthropods. [2] EPG has beentypically used to study the relationship between plants and plant-eating arthropods. EPG involves wiring insects into electrical circuits to visualizeelectrical signals associated with each insect feeding behavior. (A) By using EPG, researchers can understand how various factors affectarthropod feeding patterns. [1] Culex quinquefasciatus (Cx. quinqs.) are known vectors of virusessuch as Rift Valley fever and Japenese encephalitis, which cansignificantly affect veterinary and human health. To safely study how viruses affect mosquito feeding behavior,detachment from the EPG wire must be zero. Since July 2021, thedetachment rate in our studies has been 0.47%. Different wiring protocols have the mosquitoes either hanging orstanding following the attachment of EPG wires, but it is not clear ifusing one method or the other results in more insect detachments.
Keywords: Electropenetrography; Culex quinquefasciatus; Insect Detachment